Breast cancer cell coculture induces normal lung fibroblast transition to CAFs, promoting tumor cell dormancy and therapy resistance - Marika L. Klosowski; Kathryn E. Cronise; Eric P. Palmer; Kelly McAuliffe; Claire Stratton; Kelsie Sparks; Kendall T. Malmstrom; Gwyneth Knott-Byars; Qiong Zhou; Hector Esquer; Daniel V. LaBarbera; Daniel P. Regan (Proceedings of the National Academy of Sciences, 2025)
Cancer-associated fibroblasts (CAFs) shape the tumor microenvironment of primary breast tumors to promote tumor progression and therapy resistance. While the lung is a top metastatic site in breast cancer, the origins of lung metastasis-associated fibroblasts and their influence on disseminating tumor cell outgrowth and chemoresistance are poorly understood. Here, we demonstrate the applicability of 2-dimensional and 3-dimensional cocultures of primary human lung fibroblasts (LF) and breast cancer cells (BCC) as models of tumor–stromal interactions in lung metastatic breast cancer. Using these models, we find that BCC lines representing clinically relevant molecular subtypes differentially induce CAF-like phenotypes in primary LFs corresponding with their propensity for lung metastasis. Furthermore, we identify a mechanism by which juxtacrine signaling from LFs to triple negative breast cancer (TNBC) cells promotes expansion of prognostic dormant-like cell subpopulations and instigates autophagy-dependent therapy resistance via integrin and Janus kinase1/2 signaling. A high content kinase inhibitor compound library screen using this model identifies vacuolar protein sorting 34 as a therapeutic vulnerability unique to BCC-LF interaction whose inhibition can resensitize TNBC cells to chemotherapy and relieve LF-mediated extrinsic therapy resistance. Therefore, we propose coculture of primary human LFs and BCC as a reductionist model of interactions between tumor cells and lung-resident stroma and a tool for therapeutic and mechanistic discovery in lung metastatic breast cancer.